Diameter Optimization of No-Core Fiber for High Refractive Index Sensing (ELEKTRIKA- Journal of Electrical Engineering, 2024)
This study presents a simulation-based modal analysis to optimize the no-core fiber (NCF) sensor design for high refractive index (HRI) applications. The goal is to improve the sensitivity of the sensor towards HRI by solving problems in conventional optical fiber sensors (OFS), such as sophisticated fabrication methods, high fragility, and potential effects on long-term reliability. Furthermore, in previous work, most OFS applications focused on detecting mediums with a low refractive index (LRI). Hence, the goal of this study is to overcome these constraints. For this research, the Wave Optics module in COMSOL Multiphysics® software was used to optimize the NCF diameter, which ranged from 100 μm to 150 μm. Simulations include changes in the refractive index (RI) of the analyte in the surrounding medium of the sensor to analyse the efficiency of the NCF in HRI sensing completely, ranging from 1.46 RIU to 1.56 RIU. The performance is then assessed by monitoring the intensity change in the power spectrum, which reflects the reaction of leaky modes to various HRI conditions. The findings indicate that decreasing the size of the NCF sensor enhances sensitivity in detecting HRI mediums by amplifying the leakage loss of each order leaky mode, as opposed to a larger NCF diameter. This effect is due to the reduced confinement of modes in a smaller diameter NCF. The 100 μm diameter NCF has exceptional refractive index (RI) sensitivity and linearity, measuring 88.996 dB/RIU and 0.7783, respectively. Accordingly, NCF proves to be a promising candidate for utilization in HRI sensing applications, given its high sensitivity and straightforward fabrication, making it easily implementable and practical for real-world use.
Keywords: Diameter Optimization; No-core Fiber; Refractive Index; Sensor; Simulation